Avaliação dos efeitos do dessecamento sobre a comunidade de algas perifíticas na planície de inundação do alto rio Paraná. - Algarte, Vanessa Majewski (2009)
The hydrological regime is the main determinant of the structural and functional characteristics in river-floodplain systems and every anthropogenic activity, as the construction and dam operation that alters it function of force affects the environment so much, as the communities there existent. Because the hydrological regime of the floodplain from upper Paraná river to be considered regulated artificially, by the operation of dams upstreams this stretch, and to cause a state of transitory desiccated the littoral areas, this study aimed at to evaluate the effect that the desiccated exercises on the periphytic algae community's structure. Under the hypothesis that the exhibition, to a short desiccated period, imposed the periphytic algae community determines alterations in its composition, richness and abundance. An experiment in situ was carried simulating the variation of the hydrometric level and exhibition this community's, that has already present equilibrium, to the desiccation. Glass sheets were used while artificial substratum and the experiment lasted, as whole, 42 days sucessional. The results of this study were divided in two chapters, the first entitled Structures of the periphytic algae community after a disturbance: an experimental approach in environment of the floodplain tropical , in which, the largest difference in the periphytic algae community's structure was registered in the first five days after the event, with increase of number the Chlorophyceae and Zygnemaphyceae taxa and decrease in the density, mainly due to the class Bacillariophyceae. In the second chapter entitled "Composition algal in the periphyton after a desiccated disturbance: persistence and resilience?" it was verified that the community's composition was substantially altered after the disturbance event, with increase of species adhered loosely and initial colonizers. Phacus curvicauda was identified as indicative of the desiccated condition.